2009
DOI: 10.1186/1757-1627-2-6462
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection of giant lipoma mimicking colonic neoplasm initially presenting with massive haemorrhage: a case report

Abstract: Lipomas of the colon are benign tumors that rarely occur. Their size ranges from 2 mm to several cm. They are usually asymptomatic but occasionally they present with clinical manifestations depending on tumor size, localization and complications, which often lead to diagnostic difficulty. A 40-year-old man presented with massive rectal haemorrhage. During colonoscopy a giant polyp of over 50 mm in its bigger diameter, with a thick stalk of 2 cm, located in the transverse colon, was revealed. Endoscopic resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…[10] Some studies have demonstrated that duodenal lipomas can occur in any part of the duodenum, of which the descending part is the most common, accounting for approximately 60% of the cases. [11] Among the 57 patients in this study, 33 duodenal lipomas were located in the descending part of the duodenum, accounting for approximately 58%, which was consistent with the findings of a previous report. Duodenal lipoma is more common in middle-aged and elderly individuals, and there is no significant difference in the incidence between men and women.…”
Section: Histological and Clinical Features Of Duodenal Lipomasupporting
confidence: 92%
See 1 more Smart Citation
“…[10] Some studies have demonstrated that duodenal lipomas can occur in any part of the duodenum, of which the descending part is the most common, accounting for approximately 60% of the cases. [11] Among the 57 patients in this study, 33 duodenal lipomas were located in the descending part of the duodenum, accounting for approximately 58%, which was consistent with the findings of a previous report. Duodenal lipoma is more common in middle-aged and elderly individuals, and there is no significant difference in the incidence between men and women.…”
Section: Histological and Clinical Features Of Duodenal Lipomasupporting
confidence: 92%
“…Although the pathogenesis of gastrointestinal lipoma remains unclear, [4] it may be related to the combined effect of inflammatory stimulation and fat accumulation, and/or abnormal secretion of gonadal hormones in the anterior pituitary [10] . Some studies have demonstrated that duodenal lipomas can occur in any part of the duodenum, of which the descending part is the most common, accounting for approximately 60% of the cases [11] . Among the 57 patients in this study, 33 duodenal lipomas were located in the descending part of the duodenum, accounting for approximately 58%, which was consistent with the findings of a previous report.…”
Section: Discussionmentioning
confidence: 99%
“…The decision whether to remove lipomas and which method is the best option either endoscopically or surgically remains controversial. 7 The general agreement is that colon lipomas <2.0 cm in diameter are more accessible for endoscopic treatment. 3 Endoscopic removal is not suggested for lesions >2.0 cm due to the high risk of complications, such as bleeding and perforation.…”
Section: Discussionmentioning
confidence: 88%
“…3 Endoscopic removal is not suggested for lesions >2.0 cm due to the high risk of complications, such as bleeding and perforation. 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation